Transparência do voto e a regulamentação legal do sistema proporcional brasileiro: accountability vertical e qualidade da democracia - Polianna Pereira dos Santos (2016)
This study has the purpose to analyze how the vote translates into political representation in Brazil's proportional system, in order to verify if the elector can translate his political decision into representation and exercise, in this manner, vertical accountability, which is an indicator of the quality of democracy. The theoretical framework of this study is Robert Dahl's understanding of a democratic society under five basic criteria, which are pointed out in his book On Democracy, from the year 2000. In this way, political institutes and their legal regulation, specifically the vote, the proportional system, the political parties and their coalitions, were taken into account. Aside from the legal regulation and the Court's interpretation of these institutes, the perspective of electors and office holders was also analyzed, together with the political parties' statutes. Next, the institutional arrangements which promote the interrelation of these institutes in the political system were compared. It was then identified that the existing institutional arrangements inhibit, and to a certain measure, thwart the translation of the electors decision into representation, in virtue of the absence of transparency of the vote under the current regulation of Brazil's electoral system. Having established this, punctual modifications to this system were suggested, highlighting the importance of developing the political culture and the trust in political institutions on a Democratic State,